Dendrimer templated bioactive glass-ceramic nanovehicle for gene delivery applications1. Issue 70 (31st July 2015) - Gupta, Nidhi; Santhiya, Deenan; Aditya, Anusha; Badra, Kishore
<x xml:space="preserve">Abstract</x> Herein, multifunctional nanocrystalline microporous 45S5 bioglass particles were synthesized using poly(amidoamine) dendrimer generation 3 as a template and evaluated for gene delivery applications.